DEVELOPMENT OF AGRICULTURAL EDUCATIONAL TOURISM (A Case Study at CV Milkindo Berka Abadi in Tegalsari Village, Kepanjen District, Malang Regency) - Eri Tristanto; Bambang Ali Nugroho; Anie Eka Kusumastuti (Agricultural Socio-Economics Journal, 2022)
Edu-tourism is one of the most developed kinds of the tourism sector. One of the examples is called Agricultural Educational Tourism of CV Milkindo Berka Abadi in Tegalsari Village, Kepanjen District, Malang Regency, East Java Province. This research aimed to determine the level of conformity between performance and importance level of marketing mix (7P), including product, price, place, promotion, people, process, and physical evidence. The method used in this research was survey. Data collection was carried out by distributing structured questionnaires to 100 participants of the educational tour package. Data were analyzed by using Importance Performance Analysis (IPA) to divide marketing mix attributes into four quadrants and find out how satisfied the consumers are with the company's performance. The results revealed that the level of conformity between performance and importance of marketing mix attributes is very conformable with a conformity level of 87,035% overall, which is 80-100%. It can be concluded that the level of conformity between performance and importance level of 7P marketing mix attributes are very conformable overall. However, the companies must continue improving marketing mix attributes to match tourist expectations in Agricultural Educational Tourism of CV Milkindo Berka Abadi.